Brown and Levinsonâ€™s Politeness Strategies on Apologizing Expression of â€œThe Princess Diariesâ€ (2001) The Movie: A Discourse Analysis - Pratiwi, E.S; Santihastuti, Asih; Sukmaantara, I Putu (Jurnal Edukasi, 2018)
This research was intended to analyze the politeness strategy employed by the characters in expressing apology based on Brown and Levinsonâ€™s politeness strategies in the movie The Princess Diaries (2001). Designed as a descriptive-qualitative research, the data was analyzed by using the descriptive method where politeness strategies proposed by Brown and Levinson (1987) was applied to see the types of politeness strategies. The data was taken from an American Comedy, Family and Romance movie entitled The Princess Diaries (2001). The result of the analysis showed that there were 15 utterances that can be classified as apologizing expression which were analyzed by using Brown and Levinson (1987) Politeness Strategies. Those 15 utterances were divided into 11 utterances using positive politeness and 4 utterances using negative politeness. Based on Brown and Levinsonâ€™s politeness strategies, positive politeness happened in a group of friend and a group of family that have close relationship with the Speaker while negative politeness used to avoid offence of the Hearer by showing respect. Thus, it is concluded that positive politeness was the most politeness strategies applied by all the characters in the movie to express apology, and all the characters who applied positive politeness strategy are female. Keywords: Politeness Strategies, Apologizing Expression, Discourse Analysis.